Integrated early childhood development using appreciative inquiry in Masaka District, Uganda to policy-makers. - UNICEF (Kampala : UNICEF)
IECD is a strategy, targeting zero to eight years old children, whic h aims for holistic development of a child. It integrates health, nutri tion, water and sanitation, psycho-social care, early learning, protect ion, and any other components which the community deem it necessary for their children's holistic development. Uganda endeavours to apply an a pproach of Al in setting up IECD. Al seeks to identify and respects wha t communities are already doing with respect to child rearing practices . The role of the approach is to maximize the impact of their existing good practices for it to eventually become best practices.
This VCD is 9 minutes produced for policy-makers to grasp IECD using Al. It contains: a) a demonstration of IECD in Masaka district, Uganda , b) a brief* process of Al
*Full description oa Al is available in another video, training vide o on appreciative inquiry in integrated Early Childhood Development in Masaka district, Uganda.
Keywords: Educational equalization -- Uganda